HUBUNGAN TINGKAT PENGETAHUAN DAN PROFESI TENAGA KEFARMASIAN TENTANG BEYOND USE DATE (BUD) OBAT PADA PUSKESMAS WILAYAH KOTA BANDA ACEH - Aulianshah, Vonna; Dewi, Desri Fitria; Pamudi, Berwi Fazri; Rasidah, Rasidah (Jurnal Riset Kefarmasian Indonesia, 2025)
Basically, the determination of the Beyond Use Date (BUD) is included in the drug information service where the implementation of drug information services is the obligation of pharmacy personnel. Beyond Use Date (BUD) of a drug is the time limit for the use of a drug product after it has been formulated or prepared or after the primary packaging has been opened or damaged. The purpose of this study is to find out the relationship between the level of knowledge and profession of pharmaceutical personnel about drug BUD at the Banda Aceh City Health Center. This study is a descriptive analysis with a cross-sectional design to relate the research variables, namely the level of knowledge and profession of health workers, based on their level of education. The sample in this study is pharmacy personnel, including pharmacists and pharmaceutical technical personnel totaling 39 responders. The measuring tool used is a questionnaire. The results of the study showed that the level of knowledge of respondents was generally in the good category. Through statistical tests, significant results > 0.05 were obtained, which showed that there was no relationship between the level of knowledge and profession of pharmaceutical personnel at health centers in the Banda Aceh area.